2020
DOI: 10.1111/obr.13083
|View full text |Cite
|
Sign up to set email alerts
|

Should patients with obesity be more afraid of COVID‐19?

Abstract: Summary COVID‐19 crisis has lasted since the late 2019 to the present day. The severity of the disease is positively correlated with several factors, such as age and coexisting diseases. Furthermore, obesity is increasingly considered as a yet another risk factor, particularly, because it has been observed that people suffering from excessive body weight may experience a more severe course of COVID‐19 infection. On the basis of current research, in our nonsystematic review, we have investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 91 publications
1
47
0
6
Order By: Relevance
“…Obesity impairs the ability of the adaptive immune response to cope with viral infection [ 22 ]. AT synthesizes a number of pro-inflammatory adipokines and cytokines, including interleukin (IL)-6 and IL-8, which may weaken the antiviral immune response in obese patients [ 23 ]. Furthermore, the metabolic comorbidities of obese patients, such as diabetes, could contribute to the risk of developing severe COVID-19, although the present study adjusted for possible confounding metabolic diseases, including diabetes and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity impairs the ability of the adaptive immune response to cope with viral infection [ 22 ]. AT synthesizes a number of pro-inflammatory adipokines and cytokines, including interleukin (IL)-6 and IL-8, which may weaken the antiviral immune response in obese patients [ 23 ]. Furthermore, the metabolic comorbidities of obese patients, such as diabetes, could contribute to the risk of developing severe COVID-19, although the present study adjusted for possible confounding metabolic diseases, including diabetes and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“… 65 The pressure exerted by abdominal adiposity on the lungs, through the diaphragm, also acts to limit the movement of respiratory muscles, with less oxygen saturation 66 and worsening clinical presentation due to the lower lung volume of obese patients. 67 In addition, some comorbidities linked to obesity may contribute to a higher risk of pulmonary infections, such as the presence of asthma, which is highly prevalent among obese children, 68 and obstructive sleep apnea. 69 Regarding asthma, the same inflammatory mechanisms linked to leptin and IL-2, which explain the high prevalence and severity of this disease in obese children, 70 are also involved in the severity of COVID-19.…”
Section: Pathophysiology Of Obesity and Its Relationship With Covid-1mentioning
confidence: 99%
“…Recent studies from Europe, the United States and China have identified obesity as an independent risk factor for the most severe outcomes of COVID‐19, including death 6‐14 . A nationwide Danish study 6 of 11 122 individuals with a positive polymerase chain reaction test for SARS‐CoV‐2 found hospitalization rates of 20% among all patients and 29% among patients with overweight or obesity.…”
Section: Introductionmentioning
confidence: 99%